Odpowiedź:
[tex]P(A\cap B)=\frac{11}{30}\\P(A/B)=\frac{7}{30}[/tex]
Szczegółowe wyjaśnienie:
[tex]P(A')=0,4=\frac{2}{5}\\P(A)=1-P(A')=1-\frac{2}{5}=\frac{3}{5}\\P(B)=\frac{3}{5}\\P(A\cup B)=\frac{5}{6}[/tex]
Skorzystam ze wzoru:
[tex]P(A\cup B)=P(A)+P(B)-P(A\cap B)\\\frac{5}{6}=\frac{3}{5}+\frac{3}{5}-P(A\cap B)\\\frac{5}{6}=\frac{6}{5}-P(A\cap B)\\P(A\cap B)=\frac{6}{5}-\frac{5}{6}=\frac{36}{30}-\frac{25}{30}=\frac{11}{30}\\P(A/B)=P(A)-P(A\cap B)=\frac{3}{5}-\frac{11}{30}=\frac{18}{30}-\frac{11}{30}=\frac{7}{30}[/tex]